2005
DOI: 10.1111/j.1572-0241.2005.41109.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid and Duodenogastroesophageal Reflux after Esophagectomy with Gastric Tube Reconstruction

Abstract: Reflux symptoms represented a poor indication of esophagitis in patients with esophagectomy and gastric tube reconstruction. Simultaneous 24-h pH and bilirubin monitoring can help in identifying patients at high risk for reflux esophagitis, as well as indicating the cause of esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 27 publications
6
46
1
2
Order By: Relevance
“…If the esophagus and/or gastric tube cannot be preserved, continuity of the gastrointestinal tract may be reconstructed with, for example, colonic or small bowel interposition [7] . No significant relationship has been found between reflux symptoms, such as heart burn and regurgitation, and endoscopic findings after esophagectomy in the previous reports [3,8] . Patients with denervated stomach may be free from symptoms of gastric ulcer.…”
Section: Discussionmentioning
confidence: 82%
“…If the esophagus and/or gastric tube cannot be preserved, continuity of the gastrointestinal tract may be reconstructed with, for example, colonic or small bowel interposition [7] . No significant relationship has been found between reflux symptoms, such as heart burn and regurgitation, and endoscopic findings after esophagectomy in the previous reports [3,8] . Patients with denervated stomach may be free from symptoms of gastric ulcer.…”
Section: Discussionmentioning
confidence: 82%
“…As a consequence, there has been found up to 20% esophagitis in the cervical esophageal stump during the first year after surgery, and approximately 70% in the seventh year, and the presence of Barrett's esophagus in the cervical stump in up to 27.7% of cases, which is more serious 26,34 . Of course, the destruction of reflux containment mechanisms (loss of inferior esophageal sphincter mechanism, cardia and pylorus), promote mixed reflux (acid and bile), extremely harmful to the esophageal mucosa 36,37 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Hashimoto et al [12] also noted that gastric acidity d id not decrease after esophagectomy and the postoperative acidity in the gastric tube was high in patients with high preoperative acidity. Yuasa [13] suggested that the simu ltaneous analysis of pH and biliopancreatic reflu x is useful for determin ing the cause of the severity of the mucosal damage in the esophageal remnant. The gastric transplant recuperates its acid production with time.…”
Section: Esophageal Exposure To Acid and Duodenal Juicementioning
confidence: 99%